1999
DOI: 10.1590/s0036-46651999000300002
|View full text |Cite
|
Sign up to set email alerts
|

A ten-year survey of onychomycosis in the Central Region of the Rio Grande do Sul, Brazil

Abstract: Onychomycosis is a common infection of the nail plate caused by fungal microrganisms, and represents approximately 50% of nails disorders and 30% of all superficial mycotic infections. We present a study of the frequency, epidemiology and clinical aspects of onychomycosis in the central region of Rio Grande do Sul during the period 1988-1997.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
23
3
12

Year Published

2006
2006
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(50 citation statements)
references
References 14 publications
10
23
3
12
Order By: Relevance
“…1,[4][5][6][7][8][12][13][14][15] Fatores como condições climáticas, práticas sociais, deslocamentos cada vez mais freqüentes e hábitos de higiene certamente contribuem para as variações epidemiológicas dos dermatófitos.…”
Section: Discussionunclassified
See 2 more Smart Citations
“…1,[4][5][6][7][8][12][13][14][15] Fatores como condições climáticas, práticas sociais, deslocamentos cada vez mais freqüentes e hábitos de higiene certamente contribuem para as variações epidemiológicas dos dermatófitos.…”
Section: Discussionunclassified
“…As onicomicoses representam de 18 a 40% das onicopatias 4 e têm sua prevalência aumentada em adultos e idosos, principalmente em pacientes com diabetes mellitus. 8,[12][13][14][15][16][17] Outras situações, ou doenças de base, contribuem para o aparecimento de dermatofitoses, como em pacientes com Aids, síndrome de Down, uso de corticosteróides e drogas imunossupressoras em transplantados. 17,18 O grupo é composto pelos gêneros Trichophyton sp, Microsporum sp e Epidermophyton floccosum, que podem ser diferenciados de acordo com as características macroscópicas e microscópicas das culturas.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…In the south of the American continent the disease more frequently occurs in the humid autumn or in summer (Mackinnon et al 1969, Lopes et al 1999, whereas in Mexico the highest incidence is observed in cold and dry seasons (González-Ochoa 1965). No seasonal difference, however, has been reported by other authors (Vismer and Hull 1997, Lyon et al 2003, Barros et al 2004.…”
Section: Epidemiologymentioning
confidence: 99%
“…Generally, infection results from inoculation of the fungus through thorns, splinters, scratches and small traumas during leisure and occupational ac- tivities such as floriculture, horticulture, gardening, fi shing, hunting, farming and cattle raising, mining, and wood exploration (Mackinnon et al 1969, Mayorga et al 1978, Read and Sperling 1982, Rippon 1988, Kauffman 1999, Lopes et al 1999, Pappas et al 2000, Barros et al 2003. Laboratory professionals can be infected accidentally while manipulating S. schenckii cultures (Thompson andKaplan 1977, Cooper et al 1992).…”
Section: Epidemiologymentioning
confidence: 99%